Peran manajemen strategi dalam pengembangan produk asuransi syariah untuk meningkatkan kepercayaan masyarakat: Problematika - Awalina, Putri Nazalia (Maliki Interdisciplinary Journal, 2025)
Islamic insurance (takaful) is a non-bank financial institution that plays a strategic role in providing risk protection based on the principles of mutual help (ta’awun) and shared responsibility (takaful). However, public trust in Islamic insurance products remains lower than in conventional insurance. This study aims to analyze the role of strategic management in developing Islamic insurance products to increase public trust. The research method uses a qualitative descriptive approach with literature studies from academic sources and industry data. The results show that effective strategic management through product innovation, financial literacy improvement, fund management transparency, and digital transformation can strengthen public trust in Islamic insurance. Furthermore, regulatory support from the Financial Services Authority (OJK) and collaboration with other Islamic financial institutions play an important role in expanding market share and building a positive reputation for the Islamic insurance industry in Indonesia.